Nasogastric/nasoenteric catheter in the adult ICU: best practices implementation project. Issue 4 (26th December 2021) - Pinheiro, Patrícia A.P.C.; Brancaglione, Bruna F.; Altino, Denise M.; da Silva Santana, Flávio H.; Silva, Sidnei S.; Gomes, Vanessa R.; de Brito Poveda, Vanessa; de Araújo Püschel, Vilanice A.
ABSTRACT: Background: Good-quality nursing care is usually associated with decreased risk of harms or adverse events and improved nutritional status in patients. It is important to prevent an increased risk of infection, mortality, and hospital costs in patients, along with a rework for the nursing team. Objective: To implement best evidence-based practices in the management of the nasogastric catheter in patients admitted to adult clinical intensive care. Method: The methodology used for this study was based on that of the Joanna Briggs Institute, using the audit and feedback tools JBI Practice Application of Clinical Evidence System and Getting Research into Practice. A base audit was performed, which screened for the education of the nursing team aimed at the knowledge of the best practices, approaching the barriers related to nonadherence to the best practices and a follow-up audit. Results: The results of the base and follow-up audit showed positive variation in the percentage of adherence to the best practices proposed after the education of the nursing team. The implemented criteria that showed the greatest impact in practice ( P < 0.001) were related to insertion and checking of the catheter and maintenance of the device with adequate lavage technique. Conclusion: The results obtained from adherence to the best practices contributed to the enhancement of care related to catheter insertion, its maintenance, and withdrawal. Changes were made to the local care protocol, with care being taken to measure the exteriorized portion and to increase the frequency of catheter lavage. It is necessary to invest in the record in the chart of the care related to the management of the catheter to confirm the care provided and to assist in the clinical audit process. The results obtained can also be compared with the nutritional indicators.